Indonesian Students’ Interest on Face to Face and Anonymous-Peer Review in Writing Class - Abdul Aziz; Vebrianti Umar; Memy Wardani Elthia; Tati Akhbaryah; Wenda Septiawan (International Journal of Educational Technology Research, 2023)
Peer review as a potential pedagogical practice, has gained popularity in university writing classes for ESL/EFL students. The focus in this study is to find out what students prefer to use face-to-face peer review or anonymous peer review. This study uses a survey research approach as a methodology, the data is carried out by distributing questionnaires to students. The participants are students of SMAN 3 Banjarmasin IPA grade 11. The results of the survey data analysis of student interest in the use of face-to-face and anonymous peer techniques 59.4% or 19 students prefer anonymous to face-to-face peer review while 40.6% or 13 students choose face-to-face peer review as the best technique in providing feedback in class writing. This data was obtained from a questionnaire given to 32 people.